Glass-production Workshop of the Hunnic Times Near Komariv on the Dnister River - Oleg Petrauskas; Ruslan Shyshkin (Archaeologia Polona)
The article presents materials from the glass-production workshop of the Hunnic times found near Komariv on the middle Dnister, which was the only such workshop on the territory of European Barbaricum. In 2021, we investigated a buried structure, where remains of mostly semi-finished glass products, production waste, and finished vessels were found. Fragments of Cherniakhiv culture wheel-made pottery and hand-made vessels; Roman amphorae; coins; fibulae; a mirror; an arrowhead, etc. also come from the building. The nature of the glass finds indicates that the structure, dated to the mid-5th century AD, was associated with glass production. The workshop, built in the same period as a building on a stone foundation, could have formed a single complex. The finds and the object’s dating are evidence that glass processing was practiced also in the Hunnic times in the Cherniakhiv culture.